Zoea Crab Larva Counter (CLARCO) Based On Image Processing With Adaptive Gaussian Filter Algorithm And Blob Detection Technique - Zakiyabarsi, Furqan; Arizal, Arizal; Nurul Puteri, Annisa; Zulfajri S, Achmad; Syafaat, Muhammad (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
The size of crab larvae is very small, so there is no accurate and easy-to-use crab larvae counting tool at an affordable price. The low larval survival rate is due to the unknown larval stocking density, which causes cannibalism, a feed-to-larvae ratio that is out of proportion to the number of larvae needed to maintain water quality, a water supply that is out of proportion to stocking density, and is economically unfavorable in terms of cultivation, feed management, maintaining water quality, and the buying and selling process. Accurately estimating the amount of crab larvae is anticipated to boost their survival rate and make them more economically successful. This research is a continuation of previous research with the addition of different methods using adaptive gaussian filter algorithms and blob detection techniques to count crab larvae in the zoea-2, zoea-3, and zoea-4 phases where an increase in accuracy was obtained with an average of 97.67 %.